Is Health Practitioner Regulation Keeping Pace with the Changing Practitioner and Health-Care Landscape? An Australian Perspective - Wardle, Jonathan Lee; Sibbritt, David; Broom, Alex; Steel, Amie; Adams, Jon (Frontiers in Public Health, 2016)
Health care delivery is undergoing significant evolution and change. Task substitution has resulted in some practitioner groups expanding their scope of practice by assuming more complex clinical roles, new practitioner groups have emerged and consumer-driven demand has changed the way the public engage with health practitioners and the way many healthcare services are delivered. Using Australia as a case study, this paper explores the issue of the hesitancy to include new professions in health professions regulation schemes. Despite the significant changes in the healthcare delivery landscape, policy development in this area has remained relatively static, with active resistance to extending formal registration to new practitioner groups. Ignoring the issue of new practitioner groups in regulatory schemes is unacceptable from a public health perspective and runs against the key public protection objectives of health practitioner regulation. Development of pathways for entry of new health practitioner groups into regulatory schemes must be developed as a matter of priority.